Meta-analysis of motor imagery therapy on swallowing dysfunction in stroke patients (运动想象疗法对脑卒中后患者吞咽功能障碍影响的Meta分析) - GUO Jiaxin (郭嘉欣); GU Yufang (谷雨芳); LIU Kaiyue (刘凯月); MENG Xuefeng (孟雪峰); SUN Yingtong (孙颖童); WEI Jinrong (魏金荣) (中西医结合护理)
Objective To systematically evaluate the effect of motor imagery therapy (MI) on swallowing dysfunction in post-stroke patients. Methods Randomized controlled trials (RCTs) on the effects of MI on swallowing dysfunction in post-stroke patients were searched from CNKI, Wanfang Data, VIP, CBM, PubMed, Web of Science, and Embase from the time of inception to November 20, 2024, respectively. Literature screening, information extraction, and quality assessment were performed by two investigators, who would conduct each operation independently in strict accordance with the predetermined enrollment criteria, and Meta-integration analysis of the data was performed using RevMan 5. 4 statistical analysis software. Results After rigorous screening, eight studies that met the criteria were included, with a cumulative sample size of 534 cases. Meta statistical analysis showed that the scores of the experimental group were lower than those of the control group in the assessment of the Wada Drinking Water Test (WST) and the Standardized Swallowing Function Assessment Scale (SSA) ［MD=-1. 19, 95%CI(-1. 68, -0. 70), P＜0. 05］［MD=- 1. 14, 95%CI(-2. 18, -0. 09), P＜0. 05］, and Swallowing Quality of Life Scale (SWAL-QOL) score was significantly better than that of the control group ［MD=1. 24, 95%CI(0. 78, 1. 71), P＜0. 05］. Conclusion Motor imagery therapy can effectively relieve dysphagia symptoms in stroke patients, and the results of this study provide theoretical support for healthcare professionals to formulate relevant rehabilitation care programs. (目的 系统评价运动想象疗法(MI)对脑卒中后患者吞咽功能障碍的影响。方法 检索中国知网(CNKI)、万方(Wanfang Data)、维普(VIP)、医学生物文献数据库(CBM)、PubMed、Web of Science、Embase等数据库中自建库至 2024 年 11 月 20 日有关MI对脑卒中后患者吞咽功能障碍影响的随机对照试验(RCT)。文献筛选、信息提取以及质量评估工作由两名研究者负责, 严格依照预先设定的入组标准, 分别独立开展各项操作, 并采用RevMan5. 4统计分析软件对数据进行Meta整合分析。结果 经过严格筛选, 共纳入8篇符合标准的研究, 累计样本量534例。Meta统计分析表明, 试验组在洼田饮水试验(WST)和标准吞咽功能评定量表(SSA)的评估中, 其得分均低于对照组［MD=-1. 19, 95%CI(-1. 68, -0. 70), P＜0. 05］［MD=-1. 14, 95%CI(-2. 18, -0. 09), P＜0. 05］, 吞咽生活质量量表(SWAL-QOL)评分明显优于对照组［MD=1. 24, 95%CI(0. 78, 1. 71), P＜0. 05］。结论 运动想象疗法可有效缓解脑卒中患者的吞咽困难症状, 该研究结果为医护人员制定相关康复护理方案提供了理论支持。)